Triple responsive room temperature luminescence, photochromism and photomagnetism in a Dy(iii)-based linear chain complex. Issue 44 (27th October 2020) - Wei, Wu-Ji; Zhang, Qian; Li, Qi; Chen, Yao-Yao; Gao, Pei; Wei, Li; Hu, Ji-Xiang; Wang, Guo-Ming
Abstract : Triple responses of room temperature fluorescence, photochromism and photomagnetism tuned by photo/thermo-switched radicals were realized in a Dy(iii )-based metal–organic complex. Abstract : A Dy(iii )-based linear chain compound was reported with an eye-detectable and reversible photochromic phenomenon under ambient conditions. After light irradiation, room temperature luminescence response and photodemagnetization effects appeared for the first time via regulation of radicals, showing a radical-switchable property in electron transfer photochromic materials.